Substantial pharmacokinetic interaction between digoxin and ritonavir in healthy volunteers - Ding, Reinhard; Tayrouz Haffar, Yorki Antoine; Riedel, Klaus-Dieter; Burhenne, Jürgen; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E. (Clinical pharmacology & therapeutics, 2004)
Background Ritonavir is a potent in vitro inhibitor of several cytochrome P450 isozymes and ABC transporters including the efflux pump P-glycoprotein (P-gp). This study assessed the effect of repetitive ritonavir administration on digoxin distribution and total and renal digoxin clearance as a marker for P-gp activity in vivo. Methods In a randomized, placebo-controlled crossover study, 12 healthy male participants received oral ritonavir (300 mg twice daily) for 11 days. With the assumption that ritonavir steady state had been reached, 0.5 mg digoxin was given intravenously on day 3. Digoxin concentrations were determined in plasma and urine by radioimmunoassay, and plasma ritonavir concentrations were determined by liquid chromatography-tandem mass spectrometry. Digoxin kinetics was estimated by compartmental and noncompartmental analyses, by use of the area under the plasma concentration-time curve, and the corresponding digoxin amount excreted into urine was used for digoxin clearance calculations. Results Ritonavir significantly (P < .01) increased digoxin area under the plasma concentration-time curve from time 0 to infinity by 86% and its volume of distribution by 77% and decreased nonrenal and renal digoxin clearance by 48% and 35%, respectively. Digoxin terminal half-life in plasma increased by 156% (P < .01). Conclusion This inhibition of renal digoxin clearance is likely caused by ritonavir inhibition of P-gp. Its extent is considerable and similar to the effect of other potent P-gp inhibitors on digoxin disposition such as quinidine. These findings may, therefore, indicate that the pharmacokinetics of P-gp substrates sharing the renal tubular elimination pathway will be affected when combined with therapeutic doses of ritonavir in antiretroviral treatment regimens. In addition and contrarily to quinidine, these data indicate that ritonavir promotes digoxin distribution in the body. Clinical Pharmacology & Therapeutics (2004) 76, 73-84; doi: 10.1016/j.clpt.2004.02.008